Child life as a national asset - Millin, S. Shannon (Statistical and Social Inquiry Society of Ireland, 1917)
If those charitably inclined people who encourage begging in the streets, by giving an odd copper to a poorly clad child, would only realise the truth contained in Victor Hugo's words, much mischief might be averted. The charitable institutions in which our city abounds have ample means of ascertaining the truly deserving poor, and too often the street beggar does not come within that category. Money given indiscriminately in the streets would be much better devoted to the service of the poor if handed over to the Children's Clothing Society (Police Aided), or the Society for Prevention of Cruelty to Children, both of which, I am glad to say, are conducted on strictly non-sectarian lines. To assume the mantle of the prophet is at all times dangerous, and I have no desire to incur such risk. But there is one outstanding fact of the present war which gives us a ray of hope for the future, and that is the noble and self-sacrificing part which is being played by women. Let us take courage, and give women a more important part in the administration of the laws relating to child life, and it will rebound with untold blessings on the community. By such a course, I believe, we shall minimise the manufacture of criminals and paupers and direct the children of the slums into channels of usefulness, and thereby add very considerably to the nation's wealth.
Read December 17th, 1915.
Keywords: Child labour; Child welfare; Children and poverty; 314.15